Developing Mobile Career Learning Model for Electronics Engineering Vocational High School - Nurdianah, Evi; Sudira, Putu (Elinvo (Electronics, Informatics, and Vocational Education), 2022)
The objective of this study is to develop a mobile career learning model for electronics engineering vocational high school and reveal the feasibility of the developed mobile career learning model to develop electronics engineering vocational student's competencies. This research utilized research and development method that refers to the Holistic 4D model, includes four stages of development: define, design, develop and deploy with three levels of holistic design and an interactive cycle, namely analysis, design, and evaluation. The define stage includes the performance analysis observations and instructional needs assessment. The design stage includes the design evaluation stage which involves expert with the background of lecturers, principals, teachers, career experts, software experts and successful alumni. The develop stage involves a review of material experts and media experts as well as a limited trial involving students and teachers of electronics engineering vocational high school. The data collection used observation sheets and questionnaires that have been validated by experts. The data analysis used the descriptive method. The results of the study are as follows. (1) The developed mobile career learning model integrates vocational learning activities and career guidance by utilizing information technology in the form of mobile career learning media applications. (2) The developed mobile career learning model is feasible and can be used for career development of students with electronics engineering competence.